PUPILS' PERCEPTION OF THE EDUCATIONAL ROLE OF EXCURSIONS IN GEOGRAPHY TEACHING - Vuletic, Jovana; Anđelković, Slađana (Metodička teorija i praksa, 2024)
The importance of school excursions, carried out according to didactic-methodological standards, for improving the quality of the teaching process has been confirmed by numerous empirical studies and examples of good practice. However, we note that most excursions organized by schools in the Republic of Serbia are reduced to tour packages. Obviousness in geography teaching is of great importance for the development of geographical thinking and reasoning. Excursions provide a good opportunity to apply the principle of obviousness by enabling experiential learning, development of critical thinking, social skills, personality, motivation, more engagement and better performance. The purpose of the study is to investigate whether pupils recognize the educational role of excursions. The results were obtained through statistical data analysis collected using a survey technique among pupils in the SPSS 26.0 program. A suitable sample consists of fifth to eighth grade pupils from a school in Niš and an elementary school in a rural settlement near Niš. Pupils perceive the educational role of excursions, but the full benefit that excursions can provide as a type of educational activity has not been realized due to the way they are conducted.
Keywords: School excursions; geography teaching; experiential learning; , holistic development of pupils; learning outcomes